Assessing, Benchmarking and Analyzing Heating and Cooling Requirements for Glasshouse Food Production: A Design and Operation Modelling Framework. (September 2017) - Georgiou, Solomos; Acha, Salvador; Shah, Nilay; Markides, Christos N.
Abstract: Growing populations, increase in food demand, society's expectations for out of season products and the dependency of the food system on fossil fuels stress resources due to the requirements for national production and from importation of products from remote origins. Quantifying the use of resources in food production and their environmental impacts is key to identifying distinctive measures which can develop pathways towards low carbon food systems. In this paper, a modelling approach is presented which can quantify the energy requirements of heated glasshouse food production. Based on the outputs from the model, benchmarking and comparison among different glasshouse types and growers is possible. Additionally, the effect of spatial and annual weather trends on the heating and cooling requirements of glasshouses are quantified. Case study results indicate that a reduction in heating requirements of about 50%, and therefore an equivalent carbon footprint reduction, can be achieved by replacing a single glass sealed cover with a double glass sealed cover.